The Illusion in the Meanings of the Plural "Mim" in the Quranic Text and Its Impact on Meaning - نعيم محمد عباس (Thi Qar Arts Journal, 2025)
The original meaning of the plural "Mim" according to most linguists, Quran interpreters, and modern scholars is that the "Mim" indicates the plural of rational masculine only. It corresponds to the stressed "Nun" which indicates the plural of rational feminine. By referring to Quranic contexts, situational contexts, and the speaker’s intentions, we find that the plural "Mim" does not only indicate the plural of rational masculine but also holds different meanings. Linguistic and situational clues determine the precise meaning. Among these Quranic meanings is the indication of the plural "Mim" for both masculine and feminine, where the feminine is included in the masculine’s ruling. This meaning has not been pointed out by linguists despite its frequent occurrence in many Quranic contexts.